Een Belgische imamopleiding: mission impossible? - Franken, Leni (Religie & Samenleving, 2023)
Over the past decades, the number of (practicing) Muslims increased visibly in Belgium, but present church-state regulations are not adequately adapted to accommodate the diversity of Muslim communities. This has also repercussions for the training of imams. In this article, I will sketch the state of the art of this training in Belgium. In order to do so, I will start with an elaboration of church-state relations in Belgium, where Islam has been one of the seven recognized religions/worldviews since 1974. Subsequently, attention will be given to the local recognition of mosques. Furthermore, I will focus on the recent attempt to establish a ‘Belgian’ imam-training and on the reasons for its failure. Finally, some recommendations for improvement will be made.